A study on an observation of the road accident in Kuching/ Muhammad Fuad Jobli … [et al.] - Jobli, Muhammad Fuad; Julaihi, Mohamad Hanifhaswandy; Buang, Mohamad Zainal; Akon, Norlida; Pali, Stacey Kieth (2015)
Road accident always happens around the globe. The numbers of road accident keep increasing every day, every hour and every minute. Based on the research from Malaysia Road Safety Council the research made by ESCAP was based on every 10,000 vehicle and from this 248.3 accident cause death of 8.28 in Malaysia. The significant of this study is to identify the factor of road accident among the road user in Kuching. Through this significant of the study, we can relate to this study that is Road Condition, Attitude and Existing Laws. There are many factors that contributed to the road accident that is from the human error or attitude of the driver or motorcyclist itself. The attitudes of the road user become the main factors that contribute to the number of accident. There are many way how to decrease the number of road accident such as ordered more police officer to check the condition of the road especially during the festival time and during the weekend. The police department also being called in order to implement the OPS SIKAP IV in 183 location that the accident always occurred especially during the Hari Raya Celebration.